2015
DOI: 10.1080/10589759.2014.1002838
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic method to evaluate the residual properties of thermally damaged sandstone based on time–frequency analysis

Abstract: Evaluation of the residual properties of thermally damaged rocks is of vital importance for rock engineering. For this study, uniaxial compression experiments and ultrasonic tests were conducted on sandstone specimens which experienced temperature treatments of different levels, including 25, 100, 200, 400, 600, 800 and 10008C. Time-frequency analysis methods were applied to evaluate the deformation and strength properties of sandstone after being exposed to high temperature, confirming the effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Damage-strength correlation analysis. It is generally accepted that there is a positive correlation between rock strength and ultrasonic wave velocity and a negative correlation between rock strength and porosity, which many test results have confirmed (Basu and Mishra, 2014;Chatterjee and Mukhopadhyay, 2002;Dunn et al, 1973;Gupta and Seshagiri Rao, 1998;Kahraman et al, 2005;Olsen-Kettle, 2019;Wang et al, 2015;Yilmaz and Yuksek, 2009). Because ultrasonic testing and porosity is convenient and non-destructive, the relationship between the P-wave velocity, porosity and the rock damage characteristics has been extensively studied (Wang et al, 2023).…”
Section: Analysis Of Damage Mechanismsmentioning
confidence: 99%
“…Damage-strength correlation analysis. It is generally accepted that there is a positive correlation between rock strength and ultrasonic wave velocity and a negative correlation between rock strength and porosity, which many test results have confirmed (Basu and Mishra, 2014;Chatterjee and Mukhopadhyay, 2002;Dunn et al, 1973;Gupta and Seshagiri Rao, 1998;Kahraman et al, 2005;Olsen-Kettle, 2019;Wang et al, 2015;Yilmaz and Yuksek, 2009). Because ultrasonic testing and porosity is convenient and non-destructive, the relationship between the P-wave velocity, porosity and the rock damage characteristics has been extensively studied (Wang et al, 2023).…”
Section: Analysis Of Damage Mechanismsmentioning
confidence: 99%
“…Liu et al [16] used the ultrasonic technology to study the changes in internal defects of coal after loading in a quantitative manner, and provided a theoretical basis for applying this technology to determine the structural stability of coal and predict disasters related to coal or rock dynamics. Morcote et al [17][18][19][20] used ultrasonic testing to evaluate the influence of thermal effects on…”
Section: Plos Onementioning
confidence: 99%
“…Due to the presence of micro-cracks and heterogeneous mineral components, the rocks behave like low-pass filters, progressively decreasing the high frequencies of the ultrasonic wave propagating in the medium [78]. As a consequence, it is not possible to obtain a general relation between the degree of damage and the ultrasonic response, because the frequency spectrum varies with the different microstructural properties of the rocks as well as with the degree of thermal damage [79].…”
Section: Thermal Damagementioning
confidence: 99%
“…Non-linear parameter D can be described by proportional relation between spectral energy of high frequency wave (E h ), low frequency vibration (E l ) and lateral components (E s ) [80][81][82]: It is therefore concluded that ultrasound method for investigating damage conditions in stone materials is effective due to simultaneous variation of temperature in mechanical and acoustic characteristics [83] and provides a reliable measure for deciding on continued use of thermally damaged materials [42]. In fact, deformation parameters of materials that have suffered thermal damage are closely related to the characteristics of ultrasound in the time domain [78].…”
Section: Thermal Damagementioning
confidence: 99%